Left atrial function assessment by speckle tracking echocardiography in low-risk atrial fibrillation patients - Kareem Mohammed Helmy; Reda Biomy Bastwisy; Mohammed Kamal Salama; Wael Anwar Haseeb (Journal of the Pakistan Medical Association, 2023)
Objective: To compare the left atrial function utilising speckle tracking echocardiography in patients with low-risk and high-risk non-valvular atrial fibrillation. Methods: The descriptive, cross-sectional study was conducted at the cardiology department of Kafrelsheikh University Hospital, Egypt, from January 2021 to January 2022, and comprised low-risk atrial fibrillatin participants in group I, high-risk atrial fibrillatin patients in group II, and healthy controls in group III. After detailed medical history, the subjects underwent 12-lead electrocardigram, and echocardiographic assessment, including two dimensional, M-mode, tissue doppler, and speckle tracking of the left atrium. The association of left atrial strain with Congestive heart failure, hypertension, age ≥75 (doubled), diabetes, stroke (doubled), vascular disease sex category (female) score was explored. Data was analysed using SPSS 28. Results: Of the 90 subjects, there were 30(33.3%) in each of the 3 groups. The mean age among the groups was significantly different among the groups (p=0.014). Left atrial ejection fraction and left atrial strain had an overall significant difference among the groups (p<0.001). Congestive heart failure, hypertension, age ≥75 (doubled), diabetes, stroke (doubled), vascular disease sex category (female) score was negatively correlated with Left atrial ejection fraction and (p<0.001) and left atrial strain (p<0.001). Conclusion: In individuals with atrial fibrillatin, there was a significant decrease in left atrial strain and left atrial function. The use of speckle tracking echocardiography allowed for a more detailed analysis of left atrial mechanics. The correlation of left atrial strain and left atrial ejection fractionwith Congestive heart failure, hypertension, age ≥75 (doubled), diabetes, stroke (doubled), vascular disease sex category (female) score was significantly negative. Keywords: Atrial fibrillation, Electrocardiography, Echocardiography, Speckle.